ENGLISH LITERATURE INSTRUCTORS’ BELIEFS AND ACTUAL PRACTICES OF INTEGRATING WEB APPLICATIONS IN HA’IL UNIVERSITY - Khatmeh Suleiman Elgoudman; Kamariah Yunus (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This study purports to explore differences and similarities between literature instructors’ beliefs and actual practices of integrating Web applications in literature courses in Ha’il University. This study was designed as a descriptive case-study triangulating several data collection methods such as semi-structured interviews and observation. The data of the interviews and observation were analysed in themes. The results showed that a majority of instructors’ beliefs aligned well with their practices about integrating Web applications with teaching literature while one participant’s beliefs conflicted with her teaching practices. Result also supported the argument that instructor belief plays an important role in instructional decision making in the teaching practice while sometimes differed with their classroom practice. Results also revealed that the actual Web applications usage found in the four cases demonstrated positive result for the integration of Web applications. This provides evidence to support previous research results about the benefits that Web applications have in possibly connecting informal learning to the formal learning environment. On the other hand, although four individual instructors’ actual use of Web applications differed from case to case, they all believed that there were many benefits as well as challenges when integrating Web applications in literature courses. Furthermore, the results demonstrated an increasing usage trend among the four individual participants based on the estimated percentage of Web applications usage in their literature courses. Nonetheless, four participants in this study seemed to only bring out a few aspects of Web applications’ potential. To make the best of Web applications, more research is needed in identifying best practices of various Web applications in teaching literature and explaining complicated instructors’ beliefs about the effectiveness of Web applications in teaching literature.